Dampak Pertambangan Emas Terhadap Pendapatan Masyarakat di Desa Lalar Liang Kecamatan Taliwang Kabupaten Sumbawa Barat - Oktryaningsih, Rosita; Afifi, Mansur; Senopati, I Dewa Ketut Yudha (Universitas Mataram, 2024)
The purpose of this study is to analyze the impact of gold mining on community income in Lalar Liang Village, Taliwang District with a qualitative approach with a descriptive method that aims to systematically describe the facts or characteristics of a certain population or a certain field factually and carefully. Procedures for collecting observational data, interviews and literature studies. In this case, the data validity check technique used by the author is using the triangulation method. Data analysis of this interactive model includes: data collection, data reduction, data presentation and finally drawing conclusions. The results of the study show that there is an increase in the income of the mining community because mining is an additional source of income for the community to overcome the family economy. However, not all gold miners earn the same. Although it is not yet large-scale, the dynamics of the people's economy are beginning to be felt and the people's economy is improving from time to time through gold mining.